ANALISIS SEMIOTIKA COVER MAJALAH TEMPO EDISI 16 - 22 SEPTEMBER JANJI TINGGAL JANJI - Christian Fernando Matondnag, (2021)
Submission of mass information using mass media means that all of this information should not be long-winded, along with developing technology in education that affects the creativity of media activists. The media also began to compete to produce creativity to increase sales, and slowly the media began to change the appearance of the cover or part of the dialogues resulting from interviews to pamper the readers. Not only with the changing appearance, mass media such as magazines also add various colors to emphasize the essence of the headline that is being lifted. One of the media that uses the change is TEMPO magazine. Responding to this uniqueness, the researcher uses the semiotic theory of Roland Barthes which also helps researchers in revealing the meaning of denotation, connotation, and myth found on the cover of TEMPO magazine. The cover of the magazine has a deep meaning for the audience or readers and also has a characteristic in Indonesian politics. The data collection technique carried out by the researchers used interviews and observations on the cover of TEMPO magazine. According to the theory of Semiotics is understanding the meaning or symbols that exist in an image or photo and a message or information that can be conveyed to a wide audience to be able to study the theory. The results of the study found that semiotics understands the meaning of Denotation, Connotation, Myth on the cover of TEMPO magazine's edition of Promise to Live September 12-22.